Analisis Penyusutan Produk Karet O-Ring Hasil Proses Compression Molding dengan Metode Taguchi - Risdyani Nabila Basyasyah; Bayu Wiro Kurniawan; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
The rubber products industries of the automotive sector are rapidly growing in Indonesia. In the manufacturing process, rubber products are often produced with compression molding because it is cost-saving. Manufacturers of rubber products are facing an obstacle in shrinkage but often ignored because it is still in minor data. Based on this, research analysis of O-Ring shrinkage was carried out. The purpose of this research is to obtain low shrinkage results from the right combination of parameters and the influence of those parameters. The parameters in this research are the type of rubber compound, press time, and heating temperature, while the response variable is shrinkage dimensions of small, medium, and large sizes O-Ring products. The experimental design and analysis were determined based on Taguchi's method. The results oif the analysis for Small O-Ring responses showed the parameters of the optimum condition process were obtained using the TO compound, 10 minutes press time, and 165°C heating temperature. For medium O-Ring responses, the TO compound, 10 minutes press time, and 185°C heating temperature were used. For large O-Ring responses used PPS compound, 10 minutes press time, 185°C heating temperature. As for the contribution of eachparameters for small, medium and large O-Rings, respectively; the type of compound is 25.334%, - 4.5571%, 5.9050%, press time 13.615%, -8.067726%, 17.7376%, heating temperature -3.758%, 19.772%, 59700%.